POTENSI MAKROALGA PADINA AUSTRALIS (HAUCK 1887) DI BARAT SELATAN ACEH SEBAGAI AGEN INHIBITOR TIROSINASE - Mohamad Gazali; Eri Safutra; Zulfadhli Zulfadhli (Universitas Teuku Umar, 2018)
Seaweeds are marine macro algae that can be found attach to the bottom shallow coastal waters. There are three major groups of seaweeds namely brown algae (Phaeophyta), red (Rhodophyta) and green (Chlorophyta). Padina australis is one of brown algae which mostly found in the West-South of Aceh coastal Area. Seaweed contains bioactive compound which can serve as a defense from ultraviolet radiation that caused hyperpigmentation effect The purpose of this study is to analyse the tyrosinase inhibitory activity of P. australis extract from West-South Aceh. The results shown that the methanol extract of P. australis possess phytochemical properties such as flavonoids, tannin and saponin. tyrosinase inhibitory activity of P. australis methanol extract is the best extract which can be inhibit monophenolase with IC50 : 293.520 µg/ml and IC50 = 13.571.067 µg/ml in diphenolase pathway with kojic acid as positive control. Moreover, chloroform and n-hexane extract have no activity of tyrosinase inhibitor. Therefore, new finding of tyrosinase inhibitor agent from marine macroalgae P. australis give the fruitfull information for cosmeceutical industry. P. australis parts could be complementary each other in providing the raw material of cosmetic product.